Fetal Metabolomic Alterations Following Porcine Reproductive and Respiratory Syndrome Virus Infection - Malgarin, Carolina M.; MacPhee, Daniel J.; Harding, John C. S. (Frontiers in Molecular Biosciences, 2020)
PRRSV infection in third-trimester pregnant sows can lead to fetal death and abortions, although the mechanisms triggering these effects are not well understood. Since resistant and susceptible fetuses can coexist in the same litter, we propose that there may be differential mechanisms used by some fetuses to evade infection and/or disease progression. Our objectives were to investigate possible differences in the metabolome of PRRSV-infected and non-infected fetuses, as well as the interaction of altered intrauterine growth development and PRRSV infection to elucidate possible causes of fetal death following PRRSV infection. Near-term serum samples collected from fetuses on gestation day 106, 21 days post PRRSV-2 infection, were processed by direct flow injection mass spectrometry (DI-MS) and nuclear magnetic resonance (NMR) techniques. Experiment one investigated disease progression with 24 fetuses selected from each of four phenotypic groups: fetuses from non-inoculated gilts (CTRL); fetuses from inoculated gilts that escaped infection (UNINF); infected high viral load viable fetuses (INF); and infected high viral load meconium-stained fetuses (MEC). Experiment two investigated the interaction of intrauterine growth retardation (IUGR) and PRRSV infection by analyzing differences among: non-infected normal development (CON-N); CON-IUGR; PRRS infected normal development (PRRS-N); and PRRS-IUGR. Univariate and multivariate (PCA, PLS-DA) statistics determined group differences among various contrasts, and the most important metabolites associated with disease progression and fetal development. Significant differences in the metabolome were observed, especially between PRRSV-negative fetuses (CTRL and UNINF) and MEC fetuses, while INF fetuses appear to span both groups. The two metabolites with highest variable importance in projection (VIP) scores related to disease progression were alpha-aminoadipic acid (alpha-AAA) and kynurenine (KYN), having the highest concentration in MEC and INF fetuses, respectively, compared to CTRL and UNINF. In experiment two, non-IUGR fetuses were found to have increased levels of lysoPCs, PCs and amino acids compared to IUGR fetuses, while the near complete absence of lysoPCs and PCs in IUGR fetuses, even during infection, indicate a distinctive response to infection compared to non-growth retarded fetuses. Possible markers of PRRSV fetal susceptibility, such as alpha-AAA, kynurenine and lysoPCs, are presented and discussed.